The Bright Side of Abstraction: Abstractness Promoted More Empathic Concern, a More Positive Emotional Climate, and More Humanity-Esteem After the Paris Terrorist Attacks in 2015 - Fernández, Itziar; Caballero, Amparo; Sevillano, Verónica; Muñoz, Dolores; Oceja, Luis; Carrera, Pilar (Frontiers in Psychology, 2020)
Antecedents: Previous research on citizens’ reactions after terrorist events has shown that positive reactions can also emerge alongside pain and horror. Positive emotions have been widely associated with an abstract style of thinking. In the context of the Paris terrorist attacks in 2015, we explored Spanish citizens’ positive reactions—empathic concern, positive emotional climate, and esteem for humanity—and examined the relationships of these responses with an abstract (vs. concrete) style of thinking. Method: A longitudinal study was designed involving an online questionnaire that was administered ten days, three weeks, and two months after the attacks (N = 253). Results: Empathic concern and personal distress toward Parisians decreased from the weeks following the attacks to two months later, with empathic concern always being more intense than personal distress. Emotional climate was perceived as more hostile than positive, although positive feelings persisted. People reported moderately positive esteem for humanity. Individuals with a more abstract style of thinking reported greater empathic concern, a more positive emotional climate, and more esteem for humanity. Conclusions: Our results support and extend previous research showing that abstraction enhances people’s resilience, even under traumatic circumstances such as those surrounding a terrorist attack.